TechLens+: A Hybrid Approach to Recommending Research Papers - Torres, Roberto; Abel, Mara; Riedl, John (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2004: Anais do XVII Concurso de Teses e Dissertações, 2004)
In this paper, we present and test hybrid recommender algorithms that combine Collaborative Filtering and Content-based Filtering for recommending research papers. The hybrid approaches combine the strengths of each algorithm to address their individual weaknesses. We evaluated our algorithms through both offline experiments on a database of 102,000 research papers, and an online experiment with 110 users. Our results show that users value recommendations of papers, that the hybrid algorithms can be successfully combined, that different algorithms are more suitable for recommending different kinds of papers, and that users with different levels of experience perceive recommendations differently. Our results lead us to a completely tailored research paper recommender system.